1977
DOI: 10.1111/j.1365-2621.1977.tb08396.x
|View full text |Cite
|
Sign up to set email alerts
|

Extending Shelf‐life of Fresh Soybean Curds by In‐package Microwave Treatments

Abstract: Soybean curds are very perishable. The shelf-life of fresh soybean curds varied with storage temperatures. In-package microwave heating treatment of fresh soybean curds effectively extended shelf-life. Storage at 4.5"C, soybean curds pretreated with microwave heating to 65", 80" and 95°C have shelf-life of 16, 21 and 27 days, respectively, compared to 7 days in control. Decrease in pH, increase in titratable acidity, and viable counts in the soaking water accompanied decreases in quality of soybean curds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…These include the use of acetic acid as a coagulant (Lee et al. , 1990; Kim & Lee, 1992), in‐package microwave treatment (Wu & Salunkhe, 1977), use of chemical preservatives in immersion solutions (Pontecorvo & Bourne, 1978; Miskovsky & Stone, 1987; Lee et al. , 1990) and preparation of tofu with ozone‐treated soybean (Park et al.…”
Section: Introductionmentioning
confidence: 99%
“…These include the use of acetic acid as a coagulant (Lee et al. , 1990; Kim & Lee, 1992), in‐package microwave treatment (Wu & Salunkhe, 1977), use of chemical preservatives in immersion solutions (Pontecorvo & Bourne, 1978; Miskovsky & Stone, 1987; Lee et al. , 1990) and preparation of tofu with ozone‐treated soybean (Park et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some researches have studied quality improvement and shelf‐life extension of tofu. To extend the shelf‐life of tofu, microwave treatment, coagulation with organic acid and pH adjustment of immersion solutions have been tried (Wu & Salunkhe, 1977; Pontecorvo & Bourne, 1978; Champagene et al ., 1991). Pontecorvo & Bourne (1978) conducted an experiment to extend the storage stability including immersion in aqueous solutions, smoking and combinations of the above, and reported that the shelf‐life of tofu was extended to 10–15 days by smoking without refrigeration.…”
Section: Introductionmentioning
confidence: 99%
“…It would have to be practical in finding and choosing plastic materials that are a good fit for food packaging. We consider useful in further applications to select packaging materials with the best preservation of flavour as well as to predict their shelf life based upon progressive loss of desirable quality and flavour notes . It is believed that through our system, product competitiveness can be strengthened by continued support and encouragement to develop various plastic materials including functional trays, containers, blister packs, and so on.…”
Section: Resultsmentioning
confidence: 99%